The effect of near-infrared rays on the decrease in the number of adipocyte cells using the flow cytometry method - Emillia Devi Dwi Rianti; Fuad Ama (Healthcare in Low-resource Settings, 2024)
Adipose tissue, composed of adipocyte cells, can become problematic due to an increase in cell number (hyperplasia) and size (hypertrophy). To address this concern, interventions are needed to reduce these probabilities. Near Infrared (NIR) is an electromagnetic wave that affects tissues by being absorbed and penetrating them. NIR can induce cell death (necrosis or apoptosis), where cells respond to external factors causing tissue damage. The purpose of this study was to examine the effect of near-infrared rays on the decrease in the number of adipocyte cells using the flow cytometry method. This study, conducted in vitro using adipocyte cell cultures isolated from rat visceral adipose tissue, explores the effects of NIR exposure at various distances (1 cm, 2 cm, and 3 cm) for 20 minutes. Adipocyte cells were stained and examined using Confocal laser scanning microscopy (CLSM), and the percentage of cells was determined by flow cytometry. Statistical analyses were performed using One Way ANOVA and Duncan test. Significant differences (p-value < 0.05) were observed, and the Duncan test revealed variations in the percentage of living cells among control and treatment groups. The data indicated that exposure to high NIR energy with low wavelengths penetrated adipocyte cells, leading to a decrease in the percentage of cells and notable changes in cell morphology. Flow cytometry results demonstrated differences in live cell percentages, with group 2 (exposed at 2 cm for 20 minutes) being more effective, showing lower percentages of live cells. This research suggests that NIR exposure has an impact on adipocyte cell cultures, emphasizing its potential in influencing adipocyte cell behavior.